The Current Status of the Khalkh Dialect, and its Subdialects of Mongolian Language - Gerelt-Od, Batzaya (Mongolian Language and Literature Studies, 2025)
For over 100 years, Mongolian and Mongolist scholars studying the khalkha dialect of the Mongolian language itself have classified and named its subdialects differently. These variations are linked to numerous linguistic and non-linguistic factors, such as ethnic origin, historical development, migration patterns, the evolution of local dialects, national borders, political ideologies, and the advancement of dialectology. Furthermore, as any language or dialect undergoes continuous evolution, changes and transformations are always ongoing. Therefore, classifying and dividing languages and dialects is not a one-time task for a single individual; it's an ongoing process that requires periodic re-evaluation and updates. Forty to seventy years have passed since scholars from the Institute of Language and Literature of the Mongolian Academy of Sciences actively conducted research expeditions between the 1950s and 1980s. Since then, continuous population migration has occurred. It's also important to note that very few people today maintain their dialects in their pure form. Within the scope of the "Research on Mongolian Language Dialects" foundational research project, carried out by the Institute of Language and Literature of the Mongolian Academy of Sciences from 2022 to 2024, I have summarized and presented the findings of my research on the current state of the khalkha dialect. Within the Khalkha dialect of Mongolian there are four recognized subdialects. These subdialects share common territory and ethnic origin, but are distinguished by their specific phonological, morphological, and lexical features. Nevertheless, they retain the overall characteristics of the Khalkha dialect and the general features of the Mongolic language as a whole, and they conform to the norms of the standard written language. In addition, there exists an intercurrent Buriad–Khalkha dialect. This variety developed among communities where one group was ethnically Khalkha and the other consisted of Mongolized Evenki (Khamnigan). Having coexisted in the same locality for an extended period, the latter assimilated to the speech, customs, and material culture of the Buriad, while at the same time adopting features from both dialects. Furthermore, eleven branches of subdialects are identified. These generally correspond to subdivisions within the ethnic community based on clan, locality, or historical background, and they exhibit relatively minor but distinctive linguistic traits. However, they still preserve the overall characteristics of central, western, and eastern Khalkha, as well as the intermediate Buriad-Khalkha dialect, while maintaining the shared features of the Khalkha dialect area as a whole. Монгол хэлний халх аялгуу, түүний аман ба салбар аман аялгуунуудын өнөөгийн байдал Хураангуй. Эрдэмтэн судлаачид монгол хэлний халх аялгууг 100 гаруй жил судлахдаа түүний доторх аман болон салбар аман аялгуунуудыг өөр өөрөөр нэрлэж, ангилж, иржээ. Тэдгээр нь хэлэлцэгчдийн угсаа гарал, түүхэн замнал, нүүдэл суурьшил, нутгийн аялгууны хөгжил хувьсал, улс орны хил хязгаар, нутаг орны байршил, улс төрийн үзэл баримтлал, нутгийн аялгуу судлалын ухааны хөгжил гэх мэт хэлний ба хэлний бус олон хүчин зүйлтэй холбоотой юм. Түүнээс гадна аливаа хэл, аялгуу бол тасралтгүй хувьсан хөгжиж байдаг учраас аливаа хувиралт өөрчлөлт байнга үргэлжилсээр байдаг. Иймээс аялгуунуудыг ангилан хуваах ажил бол нэг удаа, нэг хүн хийгээд орхих ажил биш, тодорхой хугацаанд дахин дахин судалж, шинэчилж байх хэрэгтэй ажил юм. ШУА-ийн Хэл зохиолын хүрээлэнгийн эрдэмтэн судлаачид 1950-1980-аад онд хээрийн шинжилгээний ангиудаар олон удаа явж, идэвхтэй судалж байсан тэр үеэс хойш өдгөө 40-70 жил өнгөрчээ. 1990-ээд оноос хойш ард иргэд амьдрах газраа чөлөөтэй сонгох эрхтэй болсон учир шилжилт хөдөлгөөн тасралтгүй өрнөсөөр байна. Өдгөө нутгийн аялгуугaa цэврээр хадгалж буй хүмүүс нэн цөөрснийг ч тэмдэглэх хэрэгтэй. ШУА-ийн Хэл зохиолын хүрээлэнгээс 2022-2024 онд хэрэгжүүлсэн “Монгол хэлний нутгийн аялгууны судалгаа” сэдэвт суурь судалгааны төслийн ажлын хүрээнд миний бие халх аялгууны өнөөгийн байдлыг судалсан судалгааныхаа үр дүнг товчоолон толилуулъя. Монгол хэлний халх нутгийн аялгуун дотор: Улаанбаатарын халх, төв халх (төв халх, өвөрхангайн халх, говийн халх), баруун халх (өрнөд халх, элжигин халх, сартуул), зүүн халх (дорнод халх, дарьганга, халхажсан өвөр монгол), халх-буриадын завсрын (цонгоол, хамниган) хэмээх таван аман аялгуу байна. Түлхүүр үгс: аялгуу, аман аялгуу, салбар аман аялгуу; халх, Улаанбаатарын халх, төв халх (төв халх, өвөрхангайн халх, говийн халх), баруун халх (өрнөд халх, элжигин халх, сартуул), зүүн халх (дорнод халх, дарьганга, халхажсан өвөр монгол), халх-буриадын завсрын (цонгоол, хамниган)